Pre-Pandemic Adversity Buffers the Role of Social Loneliness in Caregiver Mental Health During the COVID-19 Pandemic - Emma Kahle Monahan; Julie S. McCrae; Simeon Daferede (Frontiers Media S.A., 2022)
Objectives: This study investigates how family profiles of risk and resilience established prior to COVID-19 are associated with changes in caregiver depression and stress 1 year after the pandemic onset, and how these associations are moderated by experiences of social loneliness.Methods: A sample of 243 caregivers in four risk and resilience profiles interviewed pre-COVID-19 were interviewed virtually in December 2020-February 2021 (during pandemic). Multi-level models were used to examine changes in mental health.Results: All caregivers reported increases in extreme stress during the pandemic. Caregivers with less relative adversity pre-pandemic showed significantly greater depression and loneliness in the pandemic compared to caregivers with higher pre-pandemic adversity. Social loneliness was a moderator of the association between pre-pandemic adversity and mental health.Conclusion: The study suggests families with more pre-pandemic adversity demonstrate coping that buffers the negative impact of social loneliness on mental health, emphasizing the strengths of these families that are assets to build upon in crisis. Families with more relative advantage pre-pandemic likely need assistance to reduce feelings of stress and depression in the face of increased social loneliness.